A CORPUS-BASED ANALYSIS OF PREPOSITIONS OF TIME AND LOCATION IN FILIPINO STUDENTS’ WRITTEN ESSAYS - Rafael Michael Paz (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2020)
One of the gremlins in ESL pedagogy are prepositions, specifically at, in, and on that direct nominal groups to general or specific moments and locations.  In the Filipino language, at, in, and on is equivalent to only one preposition: sa.  This makes the prepositions of time and location at, in, and on difficult for Filipino students to learn, and more difficult for Filipino teachers to teach.  Using a corpus of written essays in English, this study described the ways Filipino students use prepositions of time and location at, in, and on.  The analysis revealed that there is limited room for diversity and localization and idiosyncrasy in Filipino students’ utility of prepositions of time and location at, in, and on.  Results of the study, however, may be used as models in teaching prepositions of time and location at, in, and on to further strengthen Filipino students’ proficiency in using these lexical items in written communication.Keywords: Philippine English, prepositions of time and location, corpus-based analysis